1986
DOI: 10.1016/0026-0495(86)90094-6
|View full text |Cite
|
Sign up to set email alerts
|

Lipoprotein subfractions of runners and sedentary men

Abstract: Serum concentrations of lipoprotein mass by flotation rate were measured in 12 long-distance runners and 64 sedentary men by analytic ultracentrifugation. The runners had significantly lower serum mass concentrations of the smaller, denser low-density lipoprotein particles of flotation rates S f 0-7 (including the LDL-II, LDL-III, and LDL-IV subspecies), very-low-density lipoprotein (VLDL) particles of S f 20-400, and high-density lipoprotein (HDL) particles of flotation rates F 1.20 0-1.5 (predominately the H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
35
0
1

Year Published

1989
1989
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(43 citation statements)
references
References 37 publications
7
35
0
1
Order By: Relevance
“…For example, we estimate that 45 participants would be required in each group to give a 90% probability at the 5% level of significance of detecting differences of 0.8±0.96 mmol l À1 in low-density lipoprotein cholesterol concentration. [43][44][45] Our findings are in keeping with prospective studies suggesting that 'optimal' BMI is around 23 in young, white runners 46 and young white men in the general population; 47 but, these findings cannot be generalized to women, older adults and other groups. Cross-sectional data cannot be used to infer causality, but several randomized, controlled trials have found that aerobic exercise is accompanied by preferential reductions in visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 82%
“…For example, we estimate that 45 participants would be required in each group to give a 90% probability at the 5% level of significance of detecting differences of 0.8±0.96 mmol l À1 in low-density lipoprotein cholesterol concentration. [43][44][45] Our findings are in keeping with prospective studies suggesting that 'optimal' BMI is around 23 in young, white runners 46 and young white men in the general population; 47 but, these findings cannot be generalized to women, older adults and other groups. Cross-sectional data cannot be used to infer causality, but several randomized, controlled trials have found that aerobic exercise is accompanied by preferential reductions in visceral adipose tissue.…”
Section: Discussionsupporting
confidence: 82%
“…Low-density lipoprotein cholesterol was chosen as the primary outcome variable, and cross-sectional data suggest that LDL-C concentration is around 0.8 mmol·L −1 lower in habitual exercisers than sedentary men [26,27] and that the standard deviation in LDL-C concentration is around 0.96 mmol·L −1 [28]. Thus, the standardized difference is 0.8/0.96 = 0.83.…”
Section: Methodsmentioning
confidence: 99%
“…Nevertheless, these relationships are consistent with differences observed cross-sectionally when lean longdistance runners were compared to less lean sedentary men. 5 Change in large LDL may have shown no significant relationships with distance run and weight loss because measurements of large LDL are less reproducible than those for small LDL (see Appendix). Large LDL may be more variable over repeated measurements because there may be a greater number of metabolic parameters affecting large LDL levels, including rate of synthesis from LDL precursors (small VLDL and IDL), rate of conversion to small LDL, rate of uptake by hepatic receptors, and rate of exchange of large LDL between the vascular and extravascular spaces.…”
Section: Discussionmentioning
confidence: 99%